Quantum-beat imaging of the nuclear dynamics in D+2: Dependence of bond softening and bond hardening on laser intensity, wavelength, and pulse duration - Magrakvelidze, Maia; He, Feng; Niederhausen, Thomas; Litvinyuk, Igor V.; Thumm, Uwe (My University, 2009)
Based on a quantum-mechanical model, we calculate the time evolution of an initial nuclear vibrational wave packet in D+2 generated by the rapid ionization of D2 in an ultrashort pump-laser pulse. By Fourier transformation of the nuclear probability density with respect to the time delay between the pump pulse and the instant destructive Coulomb-explosion imaging of the wave packet at the high-intensity spike of an intense probe-laser pulse, we provide two-dimensional internuclear-distance-dependent power spectra that serve as a tool for visualizing and analyzing the nuclear dynamics in D+2 in an intermittent external laser field. The external field models the pedestal to the central ultrashort spike of a realistic probe pulse. Variation in the intensity, wavelength, and duration of this probe-pulse pedestal (i) allows us to identify the optimal laser parameters for the observation of field-induced bond softening and bond hardening in D+2 and (ii) suggests a scheme for quantitatively testing the validity of the “Floquet picture” that is commonly used for the interpretation of short-pulse laser-molecule interactions, despite its implicit “continuum wave” (infinite pulse length) assumption.